Identification of Influence Factors on Accuracy Control of Non-Destructive Testing for Embedded Depth of Highway Guardrail Column. Issue 4 (March 2020) - Hui, Bing; Li, Yubao; Xu, Yongli; Ran, Deqin; Shang, Yong; Guo, Qinghui
Abstract: Combined with the project example of column buried depth nondestructive testing, the influence factors of signal-to-noise ratio of column buried depth nondestructive testing are analyzed. At the same time, the control measures to improve the accuracy are put forward according to the influencing factors.